2006
DOI: 10.1210/jc.2006-1988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simvastatin and Oral Contraceptive Agent on Polycystic Ovary Syndrome: Prospective, Randomized, Crossover Trial

Abstract: Simvastatin improved endocrine/clinical aspects of PCOS and had beneficial effects on lipid profile and markers of systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 44 publications
6
69
0
1
Order By: Relevance
“…The studies of Banaszewska et al (29) and Falsetti et al (30), which were conducted to determine the effects of OCPs and ethinylestradiol together with cyproterone acetate in women with PCOS, respectively, revealed that a therapeutic intervention reduced the DHEA-S serum level; the results of both studies were consistent with our study's findings. menstrual cycle normalization.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The studies of Banaszewska et al (29) and Falsetti et al (30), which were conducted to determine the effects of OCPs and ethinylestradiol together with cyproterone acetate in women with PCOS, respectively, revealed that a therapeutic intervention reduced the DHEA-S serum level; the results of both studies were consistent with our study's findings. menstrual cycle normalization.…”
Section: Discussionsupporting
confidence: 91%
“…Banaszewska studied 48 women with PCOS and concluded that OCPs never lead to a significant reduction in the serum prolactin level (29), which was consistent with the results of this study, which found that LD consumption never lead to the significant reduction in the serum prolactin level.…”
Section: Discussionsupporting
confidence: 89%
“…A few studies have assessed the beneficial effect of simvastatin in PCOS (12,13). This study shows that in the presence of simvastatin, metformin is much more effective in reducing the T, DHEAS, clinical hyperandrogenemia (hirsutism), LH, and reversing the LH:FSH ratio in patients with PCOS.…”
Section: Discussionmentioning
confidence: 83%
“…At study conclusion, the simvastatin-treated women enjoyed a 12% reduction in testosterone, an elimination of the triglyceride elevation seen with the OC alone, and a significant reduction in LDL. The groups did not differ in terms of HDL [37]. In another study of obese women with PCOS, atorvastatin was found to lower testosterone while beneficially impacting both LDL-C and triglycerides [38].…”
Section: Hmg-coa Reductase Inhibitors (Statins)mentioning
confidence: 87%